Keterikatan Pengepul Dan Perilaku Fomo (Fear Of Missing Out): Studi Fenomenologi Ledakan Produksi Kapulaga Terhadap Keberlanjutan Hidup Petani di Desa Burno, Kecamatan Senduro, Kabupaten Lumajang - Aisyah Zahra Apriladianti; Chabib Musthofa (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Desa Burno in Lumajang has experienced a significant surge in cardamom cultivation in line with evolving agricultural trends. While initially boosting farmers' incomes, this production explosion has led to a drastic decline in cardamom prices in the market. This phenomenon is exacerbated by the dominance of middlemen who control pricing and marketing, making it difficult for farmers to obtain fair prices. This article explores the dynamics of the cardamom market in Desa Burno, including the impact of mass planting trends on prices and the limitations faced by farmers due to middlemen influence. Through qualitative analysis, market data, and structured interviews, this research uncovers the challenges faced by cardamom farmers and provides recommendations for fairer marketing strategies. Additionally, the FOMO (Fear of Missing Out) behavior among farmers has contributed to the increased cultivation of cardamom, further worsening the market situation. This study aims to provide deeper insights into the relationship between cardamom agriculture, middlemen dominance, and FOMO behavior, while offering solutions to enhance the welfare of farmers in Desa Burno.